Restaurant-based intervention to facilitate healthy eating choices and the identification of allergenic foods at a family-oriented resort and a campground - Lucia Tarro; Magaly Aceves-Martins; Yolanda Tiñena; Joan Lluís Parisi; Xavier Blasi; Montse Giralt; Elisabet Llauradó; Rosa Solà (BMC, 2017)
Abstract Background Restaurant-based interventions can be an enjoyable way to encourage healthier eating choices by all members of a family. Thus, the principal aims of this study were a) to promote healthy diets by increasing healthy food offerings and b) to increase the number of foods offered specifically as gluten-free and lactose-free and to inform patrons by including nutritional and allergen information that complies with Regulation 1169/2011 regarding the food served in restaurants, takeaways and snack bars. Methods A restaurant-based intervention was implemented at 16 food establishments at 2 resorts (the Cambrils Park Resort and Camping Sangulí, Spain, from 2014 to 2015) based on the following 4 components: 1) providing nutritional and allergen analyses of the offered dishes, 2) increasing the number of healthy food choices, 3) identifying menu items associated with allergies and intolerance, and 4) training staff on healthy eating and allergens. Customer satisfaction regarding food aspects was assessed using surveys (10-point scale). Results Both resorts significantly increased their offerings of healthy dishes (28.6% to 44.7%; P = 0.003) and desserts with fruit (20% to 51.3%; P = 0.013), thus obtaining the Spanish Government's Mediterranean Diet certification. Additionally, both resorts obtained Catalan Celiac Association certification. Moreover, both resorts significantly increased their percentages of gluten-free dishes (2.1% to 50.5%; P < 0.001) and lactose-free dishes (5.5% to 37.5%; P < 0.001) after the intervention. Customer satisfaction increased (mean ± standard deviation) from 6.9 ± 1.6 to 8.5 ± 1.5 (P < 0.001). Conclusion This restaurant-based intervention expanded the number of healthy and allergen-free foods offered in a family-oriented holiday resort environment to encourage healthy food choices, resulting in increased customer satisfaction.